Encadrer des thèses : d’abord, ne pas nuire. (2) Diriger c’est enseigner - Myriam Houssay-Holzschuch; Renaud Le Goix; Camille Noûs (EchoGéo)
(1) The relationship between the supervisor and the doctoral student is an important dimension of our professional activity, yet it is little analyzed. This first paper combines a reflection on the vocabulary (director, advisor, boss, supervisor...), the legal framework (the 2016 decree, which deeply redefines the modalities of the relationship), the existing scientific literature, and the importance of inscribing the thesis in a professional trajectory.(2) A second paper will offer a reflexive return of experience on our pedagogical practices as supervisors. Our purpose is to open up the debate within the French higher education system. The many dysfunctions that exist within the supervising relationship call us to action, ethically and politically. Starting from concrete cases, and situations we encountered, we therefore try to build a pedagogical and professional proposal, to provide resources and a normative horizon for advising work. Greater advisor involvement is essential for improving the conditions of doctoral work. This is why we propose a first reference framework of the concrete tasks of the advisor: teaching and accompanying, supporting and sustaining, socializing in a scientific and disciplinary community in geography, and providing resources and mentorship.doctoral supervision, pedagogy, French higher education and research system